The Relationship Between Thanatophobia Levels and Attitudes Towards Caregiver Roles Among Nurses in the COVID-19 Period - Bakir, Nazife; Cetin, Nurdilan Sener; Demir, Cuma (Sage Publications Inc, 2022)
The current study aimed to determine the relationship between fear of death and their caregiver roles in nurses during the COVID-19. The research data were collected with the personal information form, the Thanatophobia scale, the Scale of Nurses' Attitudes to Their Caregiver Roles (SNACR), the Google Questionnaire Form. Of the nurses participating in the study, 16.1% were diagnosed with COVID-19. The current study found statistically significant differences among the thanatophobia mean scores of the groups composed according to the variables; age, gender, marital status, job position, voluntarily choosing the profession, satisfaction with the department, having had a COVID-19 diagnosis, personal assessments about their own COVID-19 knowledge, and evaluating the COVID-19 disease as fatal. In addition, there were statistically significant differences among the SNACR mean scores of the groups according to their evaluations about gender, income level, working experience as a nurse, being diagnosed with COVID-19, and their COVID-19 knowledge. The current study found no correlation between the nurses' Thanatophobia scale score and SNACR score.
Keywords: COVID-19; healthcare; thanatophobia